Managing Conflicts with Wildlife: Living with Deer - William M. Giuliano; Holly K. Ober; Lauren Watine; Raoul Boughton (EDIS, 2015)
Though deer rarely pose problems for people, it is important to understand the issues associated with deer and human-deer interactions.  This 4-page fact sheet describes the biology of Florida’s white-tailed deer, the hazards associated with deer, and how to minimize these risks. Written by William M. Giuliano, Holly K. Ober, Lauren Watine, and Raoul Boughton, and published by the UF Department of Wildlife Ecology and Conservation, December 2014.